2020
DOI: 10.1021/acsami.0c13060
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Halide Boost of Carbon Nitride for Photocatalytic H2 Evolution in Seawater

Abstract: Photocatalytic H2 evolution (PHE) from extremely abundant seawater resources is an ideal way to secure sustainable H2 for humanity, but the saline in seawater easily competitively absorbs the active sites and poisons the catalyst. Herein, a series of low-cost alkali halide (NaI, KI, RbI, CsI, CsBr, and CsCl), analogous to the saline in natural seawater, was selected to modify carbon nitride (MX-CN) through one-step facile pyrolysis with the assistance of water. MX-CN possesses a large amount of negative charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Here, the peaks located at 707 cm À1 and 725 cm À1 are assigned as the breathing modes of the triazine rings. 18,25,44 Xu et al reported the appearance of a peak at 706 cm À1 for pristine CN, whereas a peak at 726 cm À1 appeared for Cs + -modied CN. 44 According to Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the peaks located at 707 cm À1 and 725 cm À1 are assigned as the breathing modes of the triazine rings. 18,25,44 Xu et al reported the appearance of a peak at 706 cm À1 for pristine CN, whereas a peak at 726 cm À1 appeared for Cs + -modied CN. 44 According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 There are several ways to intercalate Na + or K + into GCN including the calcination of a mixture of carbon nitride precursors (cyanamide, melamine, etc.) with alkali halide, [11][12][13][14][15][16][17][18][19][20][21][22] a mixture of the prepared GCN and alkali halide, [23][24][25][26][27] a mixture of carbon nitride precursors and alkali metal hydroxide, [28][29][30][31] and a mixture of the prepared GCN and alkali metal hydroxide. 6,[32][33][34][35] Most of the studies revealed that for one or several factors, alkali metal ion doping in GCN can help increase its surface specic area, 6,11,19,20,23,29 promote its crystallinity, 15,17,22,27 enhance its light absorption, 13,[15][16][17]19,21,22,27 reduce its bandgap,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrons in the former come from an external circuit, 26,206,207 while the electrons in the latter come from the separation of electrons and holes triggered by light irradiation on a photocatalyst. [208][209][210] Cl À in NaCl solution can be oxidized into Cl 2 and OCl À at the anode under acidic and basic conditions, instead of O 2 evolution by the oxidation of water. 211,212 Although Cl 2 and OCl À produced on a large scale by the electrolysis of brine are the valuable intermediate products in the chlor-alkali industry for disinfection and bleaching, 185,211,213 their toxicity and heavy corrosiveness present a major environmental problem during hydrogen production by water splitting.…”
Section: Development Of Nacl-based Electrolytes For Producing Hydrogenmentioning
confidence: 99%
“…A similar effect was reported by Wu and co-workers to alkali halide salts in seawater, and the author attributed the promoting alkali effect to the coordination to the TEOA, thus facilitating its contact with the carbon nitride-based material. [21] As the oxidation step takes place with a faster rate constant (k 2 ), it is not the limiting step for the hydrogen evolution reaction, consequently, it is very unlikely that the alkali promoting effect previously reported is related to the alkali cation coordination to the TEOA molecule.…”
Section: The Alkali Cation Effectmentioning
confidence: 96%